Assessing mortality risk in ICU patients: An integrative review - Sousa, Ronny Batista de; Nunes, Felipe Augusto Santos; Alves, Nathan Arnaldo Roble; Bringel, Isadora Luísa Borges; Lucena da Silva, Fernanda Aparecida; Ferreira, Bianca Xavier Torres; Nascimento Sousa, Antonia Bruna do; Labre, Thiago Brilhante Pereira; Pereira Bohn, Augusto Cavalcante; Rodrigues, Francisca Deiviane Lopes; Teixeira, Kaline Feitosa Alves; Dias, Rômulo Soares; et al. (International Journal of Advanced Engineering Research and Science, 2022)
ICUs (Intensive Care Units) are characterized by a high level of specialization in health care, both in technical-scientific training and in the psychological preparation of care providers. A high proportion of deaths that occur in the ICU sector are due to two main pathologies: Sepsis and Acute Lung Injury (ALI), both represent about 38.4% of mortality in hospitalized patients. The research aggregated 175 studies selected for a thorough investigation, of which 8 met the inclusion criteria. The strengths in relation to the research would be the help of the tools that were presented in screening decisions and risk stratification in clinical studies, as an example, we have the admission UVA score and the qSOFA score that had good predictive capacity for mortality in adult patients admitted to hospital with acute infection.